Influência do fotossensibilizador azul de metileno dissolvido em etanol na terapia fotodinâmica antimicrobiana sobre o status oxidativo sistêmico e colágeno gengival em modelo experimental de periodontite - Pillusky, Fernanda Maia (2015)
The purpose of this study was to evaluate the effects of an antimicrobial photodynamic therapy (aPDT) employing the photosensitizer methylene blue dissolved in ethanol on the systemic oxidative status likewise on the gingival collagen content of rats with periodontitis. Male Wistar rats were randomly divided into two main groups: NC (negative control; no periodontitis) and the remaining animals were submitted to periodontitis induction group. In the last group, the cotton ligature was placed at the first right mandibular molar of each animal in a submarginal position to induce experimental periodontitis. The animals with periodontitis were subdivided into groups according to the periodontal treatment as follow: SRP group (scaling and root planing), aPDT I group (SRP+aPDT+MB dissolved in water), and aPDT II group (SRP+aPDT+MB dissolved in ethanol). After 7 days, the ligature was removed and periodontal treatments were performed. At 7, 15 and 30 days, rats were euthanized and gingival tissue was removed for morphometric analysis. The erythrocytes were used to evaluate systemic oxidative status. Besides that, it indicated a protective influence of aPDT II in erythrocytes already at 15 days observed by the elevation in levels of systemic antioxidant defense. The morphometric findings showed that aPDT II group was the only one that restored the percentage of total collagen area also in 15 days, as well as, aPDT II group recovered the type I collagen area at the same time-point. According to this study we could suggest that aPDT employed as an adjunct to the standard treatment of periodontitis (SRP) increases systemic protective response against oxidative stress periodontitis-induced facilitating and accelerating the periodontal healing particularly when methylene blue is dissolved in ethanol.